Electroacupuncture alleviates pain after total knee arthroplasty through regulating neuroplasticity: A resting‐state functional magnetic resonance imaging study - Bingxin Kang; Chi Zhao; Jie Ma; Haiqi Wang; Xiaoli Gu; Hui Xu; Sheng Zhong; Chenxin Gao; Xirui Xu; Xinyu A; Jun Xie; Mengmeng Du; et al. (Brain and Behavior, 2023)
Abstract Introduction We aimed to evaluate the efficacy of electroacupuncture in relieving acute pain after total knee arthroplasty (TKA) and related mechanism. Methods In this randomized, single‐blind, and sham‐acupuncture controlled study. Forty patients with postoperative acute pain were recruited and randomly divided electroacupuncture group (n = 20) and sham‐acupuncture group (n = 20) from November 2020 to October 2021. All patients received electroacupuncture or sham‐acupuncture for 5 days after TKA. Their brain regions were scanned with resting‐state functional magnetic resonance imaging before and after intervention. Pain was scaled. Another 40 matched healthy controls underwent scanning once. The amplitude of low‐frequency fluctuation (ALFF) values was compared. Pearson's correlation analysis was utilized to explore the correlation of ALFF with clinical variables in patients after intervention. Results Compared with the HCs, patients with acute pain following TKA had significantly decreased ALFF value in right middle frontal gyrus, right supplementary motor area, bilateral precuneus, right calcarine fissure and surrounding cortex, and left triangular part of inferior frontal gyrus (false discovery rate corrected p < .05). Patients had higher ALFF value in bilateral precuneus, right cuneus, right angular gyrus, bilateral middle occipital gyrus, and left middle temporal gyrus after electroacupuncture (AlphaSim corrected p < .01). Correlation analysis revealed that the change (postoperative day 7 to postoperative day 3) of ALFF in bilateral precuneus were negatively correlated with the change of NRS scores (r = −0.706; p = .002; 95% CI = −0.890 to −0.323) in EA group. Conclusions The functional activities of related brain regions decreased in patients with acute pain after TKA. The enhancement of the functional activity of precuneus may be the neurobiological mechanism of electroacupuncture in treating pain following TKA.